The effect of (TABATA) exercises on some physiological abilities and shooting skill performance in basketball for juniors (Journal of the College of Basic Education, 2023)
Summary of the research:The importance of the application of Tabata exercises was one of the methods of high-intensity interval training (HIIT) proposed based on the performance of training stresses based on doing intense, fast and repeated exercises in a short time and taking fast intervals of rest between these exercises, and it has effective effects on the aerobic and anaerobic energy system The researcher used the experimental method for one experimental group on a sample of (7) players from the Al-Karkh 2 breeding team. The research sample was chosen randomly, and the researcher conducted pre-tests, which are the lactic ability test, measuring the blood oxygen saturation rate, measuring the heart rate, respiratory rate, and the free throw test. By applying the proposed (TABATA) exercises for a period of (8) weeks, at two units per week, and collecting the results, the researcher reached the following conclusions: The adoption of (TABATA) exercises works to develop some physiological abilities and the skill of shooting among junior basketball players. The researcher recommended the necessity of generalizing this type of exercises